Organizational Network in the Development of Mamminasata Urban Areas, South Sulawesi Province - Widyawati Widyawati; Ida Widianingsih; Ramadhan Pancasilawan (Jurnal Ilmiah Ilmu Administrasi Publik, 2018)
This research explains the organizational network in Mamminasata urban area,  South Sulawesi Province, Indonesia. The area was formally managed by the Mamminasata Metropolitan Development Agency (BKSPMM) since its establishment. The research used descriptive research method with qualitative approach through interviews and observation on the parties involved in  managing the development of Maminasata urban area. Furthermore, the data: strengthened by secondary data review of previous research results. Analyses also  combined with  data from relevant agencies. The results indicate that there is a fragmented organization network in terms of cooperation, coordination and communication amongs involved local governments in the development Mamminasata urban area, We would argue that the tendencies of respected local governments to express their own interests occurred due to the absence of cooperation and coordination mechanisms. Furthermore, ineffective communication amongs local governments led to the inconsistency of local development planning documents.